Mengandung Bawang, Iklan Gojek Mengajak Masyarakat untuk Berbagi Kasih dan Tangis Kebahagiaan di Bulan Ramadan - Apriani, Calliana; Loisa, Riris; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Indonesia is a country that is rich of its diversity, race, ethnicity, ethnicity, and culture. According to data from Global Religious Futures in 2020, Muslims in Indonesia reached 229 million people or 87% of the total population of Indonesia. This shows the importance of Islam and all forms of traditions that exist in Indonesia, one of which is Ramadan. This study examines the meaning of creative messages in online transportation advertisements, namely the Gojek Ramadan 2021 advertisement